Dark ambitions ebook - Hannon, Irene (Code of Honor, 2019)
When former Army Night Stalker Rick Jordan hires private investigator Heather Shields to help him solve a mystery that began with a trail of blood, a callous murderer will do whatever it takes to stop them—even if it means killing again.